Pengaruh Variasi Produk, Suasana Cafe, Social Media Marketing, Dan Metode Pembayaran Terhadap Peningkatan Penjualan: Studi Kasus Pada Coffee Shop di Kabupaten Blora tahun 2022 - Yulianna Regina Ratnasari; Ira Setiawati; Noni Setyorini (Universitas Kristen Indonesia Toraja, 2024)
This research aims to determine the influence of product variations, café atmosphere, social media marketing, and payment methods on increasing sales (case study of a coffee shop in Blora district in 2022). The type of research used is quantitative (primary) research. In this research, the total sample was 161 people consisting of employees and owners, obtained using probability sampling methods. Sample data was obtained from a questionnaire. The data analysis technique used is quantitative methods. This research was processed using IBM SPSS 25 software. The results of this research are based on partial tests with the T Test and show that (1) product variations do not have a negative influence on increasing sales, (2) the café atmosphere has a positive influence on increasing sales, (3) ) social media marketing does not have a positive influence on increasing sales, (4) payment methods have a positive influence on increasing sales. Based on a simultaneous test with the F Test, it is stated that product variations, café atmosphere, social media marketing, and payment methods simultaneously influence increasing sales.